Financial Market Development and Income Inequality: A Panel Data Analysis Across Europe - Puscasu, Ela-Andrada (Technium Social Sciences Journal, 2025)
Financial market development is often seen as a driver of economic growth, yet its impact on income inequality remains debated. While some argue that financial expansion broadens access to capital and reduces disparities, others suggest it disproportionately benefits higher-income groups. Building on this debate, this paper examines the relationship between financial market development and income inequality across European Union member states, Turkey, and the United Kingdom from 2014 to 2023. Using panel data regression techniques, we assess this link through OLS, pooled OLS, fixed effects, and random effects models. Results indicate that traditional financial indicators (market capitalization, value traded, turnover ratio) have limited direct effects on inequality, while broader financial system efficiency (Financial Markets Index, Financial Development Index) correlates with lower disparities. Labor market conditions, particularly unemployment, emerge as the strongest determinant of inequality, emphasizing that financial expansion alone cannot counteract structural economic imbalances. These findings suggest that financial markets must be accompanied by inclusive labor policies, financial literacy programs, and regulatory oversight to ensure equitable economic benefits. Future research could explore the role of institutional quality and financial innovation in shaping income distribution.